Tectonostratigraphic analysis of the Late Triassic-Early Jurassic syn-rift sequence of the Neuquén Basin in the Sañicó depocentre, Neuquén Province, Argentina - D’Elia, Leandro (2012)
The initial syn-rift infill (Upper Triassic-Lower Jurassic) of the Neuquén Basin involved a complex stacking of lava, pyroclastic and sedimentary units, in which volcanic rocks compose up to 72% of the infill. The high-quality outcrops of the southern Sañicó depocentre, which was uplifted and exposed during the Andean orogeny, were studied in order to determine the lithofacies arrangements, the tectonostratigraphic framework and the main controls over the syn-rift succession. The tectonostratigraphic study made it possible to determine three sections characterized by the predominance of effusive, pyroclastic or sedimentary deposits. These sections indicate three different evolutionary stages of the volcanic rifting. The onset of this rift stage was dominated by effusive rocks with minor ignimbrite and alluvial volcaniclastic units, which indicates the occurrence of composite volcanoes at the boundaries of the depocentre. The mid-rift stage was characterized by the development of fault-controlled, large ignimbrite deposits intebedded with volcaniclastic alluvial deposits and lava units, which suggests a volcanotectonic depression related to asymmetrical and incremental subsidence. The end of the volcanic rifting event was marked by a decrease in the volume of the volcanic rocks and the occurrence of low-relief effusive aggradational volcanic edifices and lava fields in close relation with alluvial, deltaic and lacustrine units. The analysis of the synrift sequence in the Sañicó depocentre showed the complex relationships between tectonic and volcanic controls which occurred in different magnitudes and times during the rifting evolution.